2014
DOI: 10.15835/nsb629308
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic Studies on Two Himalayan Species of Traditional Medicinal Value: <i>Allium wallichii</i> and <i>Allium stracheyi<i/>

Abstract: The present research was aimed as a pharmacognostic study of whole plants of Allium wallichii and Allium stracheyi, both of which are very important traditional medicinal plants of North-West Himalayas. This study was carried out in terms of macroscopic and microscopic analyses and standard histochemical methods were followed for detecting starch, calcium oxalate, tannins, total lipids and alkaloids. Allium wallichi can be distinguished from A. stracheyi by possessing polyarch roots, mycorrhizal fungi in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Pollen grains were analyzed for various quantitative and qualitative characters (Table 2). (Gaur, 1999) Himalayan region of India, Pakistan, Bhutan, and Tibet, 1500-3300 m asl (Balkrishna, 2012) Gangnani, Uttarakhand 2199 30°56.14ˈ 78°41.08ˈ Asparagales Amaryllidaceae Amaryllidaceae Amaryllidaceae Amaryllidaceae Allium stracheyi Baker/23772 23772 23772 23772 Farn Endangered (Mohan et al, 2019) Western Himalaya in India, Nepal and Pakistan, 2500-3625 m asl (Singh and Sanjappa, 2006;Rawat et al, 2016;Tiwari et al, 2014) Saroli The Himalayas in India, Cultivated in India (Chopra et al, 1956;WOI, 2000) CSIR-IIIM, Jammu, J&K Inner ranges of the Himalaya from Kashmir to Sikkim; 1800-4000 m asl (Gaur, 1999;Khare, 2007) Chattergalla, Doda, J&K 3125 32°52.69ˈ 075°43.65ˈ…”
Section: Methodsmentioning
confidence: 99%
“…Pollen grains were analyzed for various quantitative and qualitative characters (Table 2). (Gaur, 1999) Himalayan region of India, Pakistan, Bhutan, and Tibet, 1500-3300 m asl (Balkrishna, 2012) Gangnani, Uttarakhand 2199 30°56.14ˈ 78°41.08ˈ Asparagales Amaryllidaceae Amaryllidaceae Amaryllidaceae Amaryllidaceae Allium stracheyi Baker/23772 23772 23772 23772 Farn Endangered (Mohan et al, 2019) Western Himalaya in India, Nepal and Pakistan, 2500-3625 m asl (Singh and Sanjappa, 2006;Rawat et al, 2016;Tiwari et al, 2014) Saroli The Himalayas in India, Cultivated in India (Chopra et al, 1956;WOI, 2000) CSIR-IIIM, Jammu, J&K Inner ranges of the Himalaya from Kashmir to Sikkim; 1800-4000 m asl (Gaur, 1999;Khare, 2007) Chattergalla, Doda, J&K 3125 32°52.69ˈ 075°43.65ˈ…”
Section: Methodsmentioning
confidence: 99%
“…For a long, the plant is very useful and highly neglected during current research. Only few studies including pharmacognostic and phylogenetic have been carried out in past 7,10,39 . However, no any studies so far conducted for revealing the stomata type, stomata number and stomatal index.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several species of Allium genus including onion and garlic are mostly utilized for the source of vegetable and medicine throughout world. Among these Allium wallichii Kunth (Family: Amaryllidaceae; Locally known as Jimbu or Himalayan onion) are one such fewer known species (with rare and endangered status in some places) having high medicinal and culinary value and are commonly used by Himalayan tribal communities (Tiwari et al 2014;Mohan et al 2019). As per records, Allium polyastrum, Allium bulleyanum and Allium praelatitium are some of the common synonyms known for the plant (Quattrocchi 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, A. wallichii is a perennial herb of higher altitude (between 2700 to 3600 m elevations) having single, conical, and short bulb (flowering during August and September and having garlic like odor), majorly habitat in Bhutan, India, Myanmar, Nepal and Southwestern China, respectively (Chhetri & Gupta 2007, Rana & Samant 2010, Huang et al 2014Chen et al 2021). The detailed pharmacognostical and phylogenetic studies revealing various identification characters has been carried out in the recent past (Tiwari et al 2014, Huang et al 2014, Paul et al 2019, Tang et al 2021. A study conducted on 110 informants suggested strong aroma for A. wallichii by 100%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation